Georgia : Request for a Stand-By Arrangement and an Arrangement Under the Stand-by Credit Facility: Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Georgia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This staff report considers Georgia's request for a Stand-By Arrangement and an arrangement under the Standby Credit Facility. Performance in 2011 has been stronger than originally envisaged, with growth of nearly 7 percent, inflation in the low single digits, public debt falling to 34 percent of GDP, and international reserves increasing to USD 2.8 billion. Exchange rate flexibility remains a critical instrument of adjustment in response to shocks. At the same time, high financial dollarization may require the central bank to intervene to avoid abrupt, and potentially destabilizing, exchange rate fluctuations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet